Identity through Urban Nomenclature: Eight Central European Cities - Stiperski, Zoran (Array, 2011)
This paper deals with identity through city toponyms. Names of streets, squares, parks and lanes provide insight into a community’s interpretation of its past, determined in relation to individuals, institutions and events. Street terminology becomes a pantheon of meritorious social icons. Changes indicate the trends, goals and aspirations of society. This study was conducted in the historical cores of eight Central European cities: Graz, Kraków, Olomouc, Prague, Maribor, Zagreb, Zadar and Mostar. Three time cross-sections were examined: 1935, 1985 and 2009. The year 1935 was an example of the social conditions before WWII and socialist revolutions in Eastern Europe. The period after the socialist era was reflected in 1985. The year 2009 represents the present situation (transition situation). WWII had more of an effect on urban nomenclature than the fall of the Berlin Wall. The authors, in their conclusions, indicate differences in this general conclusion between various cities. Finally, regarding the structure of toponyms, they conclude that ‘statehood’, ‘culture- creators and artists’ and ‘religion’ are overall the three most emphased ‘origins’ of toponyms, yet there are differences between cities, and in some other types of toponyms are more dominant (derived from localities, ‘crafts and trades’, ‘entrepreneurs’).